Adipose tissue knockdown of lysozyme reduces local inflammation and improves adipogenesis in high-fat diet-fed mice. (April 2021) - Latorre, Jèssica; Lluch, Aina; Ortega, Francisco J.; Gavaldà-Navarro, Aleix; Comas, Ferran; Morón-Ros, Samantha; Rodríguez, Amaia; Becerril, Sara; Villarroya, Francesc; Frühbeck, Gema; Ricart, Wifredo; Giralt, Marta; et al.
Abstract: Chronic systemic low-level inflammation in metabolic disease is known to affect adipose tissue biology. Lysozyme (LYZ) is a major innate immune protein but its role in adipose tissue has not been investigated. Here, we aimed to investigate LYZ in human and rodents fat depots, and its possible role in obesity-associated adipose tissue dysfunction. LYZ mRNA and protein were identified to be highly expressed in adipose tissue from subjects with obesity and linked to systemic chronic-low grade inflammation, adipose tissue inflammation and metabolic disturbances, including hyperglycemia, dyslipidemia and decreased markers of adipose tissue adipogenesis. These findings were confirmed in experimental models after a high-fat diet in mice and rats and also in o b/ob mice. Importantly, specific inguinal and perigonadal white adipose tissue lysozyme ( Lyz2 ) gene knockdown in high-fat diet-fed mice resulted in improved adipose tissue inflammation in parallel to reduced lysozyme activity. Of note, Lyz2 gene knockdown restored adipogenesis and reduced weight gain in this model. In conclusion, altogether these observations point to lysozyme as a new actor in obesity-associated adipose tissue dysfunction. The therapeutic targeting of lysozyme production might contribute to improve adipose tissue metabolic homeostasis. Graphical Abstract: ga1 Highlights: Lysozyme gene is highly expressed in human and mice subcutaneous and visceral adipose tissue in association to obesity. Adipose tissue lysozyme expression is linked to adipose tissue inflammation and obesity-associated metabolic disturbances. Specific adipose tissue lysozyme gene knockdown reduces adipose tissue inflammation and restores adipogenesis.